2011
DOI: 10.1136/ard.2010.143743
|View full text |Cite
|
Sign up to set email alerts
|

EULAR Sjögren's Syndrome Patient Reported Index (ESSPRI): development of a consensus patient index for primary Sjögren's syndrome

Abstract: ESSPRI is a very simple index designed to measure patients' symptoms in primary SS. It has good construct validity and is well correlated with SSI and PROFAD. ESSPRI should now be validated for use as an outcome measure in clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
298
0
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 435 publications
(308 citation statements)
references
References 16 publications
4
298
0
6
Order By: Relevance
“…19,26 Studies in oral health show that pSS patients have a diminished salivary flow with consequent high incidence of dental caries, increased susceptibility to oral candidiasis, tooth loss, greater periodontal destruction, pain symptoms during chewing, speech difficulties, tongue palpitation and angular cheilitis. 5,6,27,28,29,30,31,32 The present study demonstrated that the decreased salivary flow in pSS patients was associated with higher PI, and a significant imbalance between the concentration of pro-and anti-inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…19,26 Studies in oral health show that pSS patients have a diminished salivary flow with consequent high incidence of dental caries, increased susceptibility to oral candidiasis, tooth loss, greater periodontal destruction, pain symptoms during chewing, speech difficulties, tongue palpitation and angular cheilitis. 5,6,27,28,29,30,31,32 The present study demonstrated that the decreased salivary flow in pSS patients was associated with higher PI, and a significant imbalance between the concentration of pro-and anti-inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…using the EULAR Sjögren's Syndrome Patient Reported Index (ESSPRI), which is calculated by an arithmetic mean, and composed of 3 domains (dry mouth, fatigue and pain). 19 Gingival crevicular fluid (GCF) and salivary sample analysis…”
Section: Clinical Examinationmentioning
confidence: 99%
“…Sendo a SS uma doença sistémica com grande foco semiológico a nível oral, para profissionais de saúde revela-se importante analisar a componente oral e sistémica numa avaliação global da qualidade de vida. [9][10][11]31 Como tal, espera-se a progressão futura da investigação na área.…”
Section: Discussionunclassified
“…Disease activity was calculated according to the EULAR Sjögren's syndrome disease activity (ESSDAI) and patient reported index (ESSPRI). [3][4] A well written informed consent was received from all study participants and the study was approved by the institutional review and ethical committee.…”
Section: Patients and Controlsmentioning
confidence: 99%